Integrating Routing and Inventory Decisions in One-Warehouse Multiretailer Multiproduct Distribution Systems - Viswanathan, S.; Mathur, Kamlesh (Management Science, 1997)
We consider distribution systems with a central warehouse and many retailers that stock a number of different products. Deterministic demand occurs at the retailers for each product. The warehouse acts as a break-bulk center and does not keep any inventory. The products are delivered from the warehouse to the retailers by vehicles that combine the deliveries to several retailers into efficient vehicle routes. The objective is to determine replenishment policies that specify the delivery quantities and the vehicle routes used for the delivery, so as to minimize the long-run average inventory and transportation costs. A new heuristic that develops a stationary nested joint replenishment policy for the problem is presented in this paper. Unlike existing methods, the proposed heuristic is capable of solving problems involving distribution systems with multiple products. Results of a computational study on randomly generated single-product problems are also presented.